A study of large floods in the Thambraparani river in Tamil Nadu (MAUSAM, 1976)
The paper contains analysis of 16 synoptic situations during the period 1891-1960 (70 years) over and near the Gulf of Mannar m which prima facie, there could have been very heavy ram and consequent large floods in the Thambraparani river in the extreme south of the Indian Peninsula. It was however found that there were only 3 situations, in which 24 hours rainfall exceeding 200 millimeters at anyone station in the river catchment was recorded. In all these three cases, there were large floods in that river.The basic synoptic causes for these 3 occasions of large floods have been investigated in detail. Hydrological data pertaining to these 3 flood-situations were specially obtained from the Government of Tamil Nadu in the proforma prescribed by UNESCO for compiling information about catastrophic floods. Discharge-hydrographs based on the available data were prepared and studied. Isohyetal analyses for a one-day and two-day rainstorm were also carried out. The hydrological characteristics of the floods so far as these could be determined from the available flood-data have been discussed. All the three oases of large floods could be termed as “Flash floods". The factors that led to the very heavy rainfall and flash floods have been discussed from the point of view of issue of heavy rainfall and flood warnings on a quasi-empirical basis.